Capacitive pressure sensor with stable interface adhesion and low hysteresis as well as preparation method and application of capacitive pressure sensor

By using a combination technology of ionic gel and silicon pyramid templates in a flexible pressure sensor, the stable interface adhesion of heterogeneous materials is achieved, solving the problem of unstable interface adhesion in traditional methods, and improving the low hysteresis pressure capacitance response of the sensor.

CN119803737APending Publication Date: 2025-04-11NANJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510204877.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing flexible pressure sensors do not adhere firmly to the interface, which can easily lead to functional failure. The commonly used interface modification methods are cumbersome to operate and limited material selection.

Method used

The ionic gel precursor was prepared by mixing the ionic liquid with methyl acrylate, adding a crosslinking agent and an ultraviolet photoinitiator, and combining with the plasma dry etching of the SiO2 layer to prepare a silicon pyramid template. Spin-coated photoresist and controlling the ultraviolet exposure time were used to achieve stable interface adhesion of heterogeneous materials.

Benefits of technology

It realizes stable interface adhesion to heterogeneous materials without the need for additional crosslinking agent or surface treatment, reduces energy dissipation and improves the low hysteresis pressure capacitance response of the pressure sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119803737A_ABST
    Figure CN119803737A_ABST
Patent Text Reader

Abstract

The invention discloses a low-hysteresis capacitive pressure sensor with stable interface adhesion and a preparation method and application thereof, and belongs to the technical field of flexible pressure sensors. The method comprises the following steps: mixing an ionic liquid with methyl acrylate, adding a cross-linking agent and an ultraviolet light initiator, and stirring to obtain an ionic gel precursor; then etching the SiO2 layer by adopting a plasma dry method to prepare a silicon pyramid template; and finally, by spin-coating the photoresist and controlling the ultraviolet exposure time of the ionic gel and the photoresist, interface adhesion can be carried out on the heterogeneous material without an additional cross-linking agent or surface treatment, and the pressure sensor with a stable interface is obtained. According to the invention, interface adhesion is realized by adopting secondary exposure, so that the change amount of the contact area between the ionic gel and the ITO lower electrode in the compression process is reduced, and the energy dissipation is reduced, so that the pressure sensor realizes low-hysteresis pressure-volume response.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of flexible pressure sensors, and in particular relates to a low-hysteresis capacitance pressure sensor with stable interface adhesion, and a preparation method and application thereof. Background Art

[0002] With the rapid development of wearable devices and flexible electronic devices, as well as the continuous enrichment of application scenarios, higher requirements are placed on the reliability and robustness of the devices themselves. For flexible pressure sensors, although the sensitivity and pressure detection range have been greatly improved through structural design and material innovation, the commonly used classic sandwich structure is simply stacked, the interface is not firmly bonded, and it is easy to fall off and dislocate, causing functional failure.

[0003] The main solution currently used is to modify the interface through silane coupling agents, or to add cross-linking molecules to achieve interface adhesion. However, these methods have problems such as cumbersome operation and limited material selection. How to achieve a pressure sensor with stable interface adhesion for heterogeneous materials through a simplified preparation process is an important challenge. Summary of the invention

[0004] The first object of the present invention is to disclose a method for preparing a low hysteresis capacitive pressure sensor with stable interface adhesion, which can achieve interface adhesion of heterogeneous materials without the need for additional cross-linking agents or surface treatment.

[0005] A second object of the present invention is to provide a low hysteresis capacitive pressure sensor with stable interface adhesion, wherein energy dissipation is reduced, resulting in the pressure sensor achieving a low hysteresis pressure-capacitive response.

[0006] The third objective of the present invention is to disclose the application of the capacitive pressure sensor prepared as above in flexible electronic devices.

[0007] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0008] A preparation method of a low hysteresis capacitive pressure sensor with stable interface adhesion comprises mixing an ionic liquid with methyl acrylate, adding a crosslinking agent and an ultraviolet light initiator, and stirring to obtain an ion gel precursor; using a plasma dry etching method to etch SiO 2 layer to prepare a silicon pyramid template; by spin coating photoresist and controlling the UV exposure time of the ion gel and photoresist, the interface adhesion of heterogeneous materials can be achieved without the need for additional cross-linking agents or surface treatment, and finally a pressure sensor with a stable interface is obtained.

[0009] Furthermore, the main component of the ionic liquid is BMIM + and SPA -The ionic liquid is prepared by mixing 1-butyl-3-methylimidazole chloride and 3-sulfonate propyl methacrylate potassium salt, adding tetramethoxyphenol and dissolving in acetone.

[0010] Furthermore, the mass ratio of the ionic liquid to methyl acrylate is 1:3.

[0011] Furthermore, the crosslinking agent is HDDA, and the ultraviolet light initiator is TPO; the molar ratio of the crosslinking agent is 2.5%; and the molar ratio of the ultraviolet light initiator is 0.5%.

[0012] Furthermore, plasma dry etching of SiO 2 The method of preparing the silicon pyramid template is as follows: using RPN1150 photoresist as a mask, using reactive ion etching, working pressure 2Pa, ignition pressure 3Pa, and reaction gas CF 4 and CHF 3 , flow rates were 10 sccm and 30 sccm respectively, and the power was 100 W; using the silicon oxide pattern as a mask, the silicon wafer was etched using a 25% TMAH solution at 80°C in a water bath to obtain a pyramid silicon template.

[0013] Furthermore, photoresist RPN1150 was spin-coated on the thermally oxidized silicon wafer at 4000 rpm; and SU-8 2025 was spin-coated on the ITO / PET surface at 2000 rpm with a thickness of 50 μm.

[0014] Furthermore, the ITO / PET spin-coated with SU-8 2025 was exposed for 7 seconds using an MJB4 UV photolithography machine. The ion gel precursor attached to ITO / PET was exposed for 7 minutes using a UV lamp. The semi-cured ion gel was then laminated with the semi-exposed SU-8 photoresist and exposed for 30 minutes using a UV lamp under a pressure of 10 KPa.

[0015] Furthermore, the preparation method of the low hysteresis capacitive pressure sensor with stable interface adhesion comprises the following steps:

[0016] (1) 1-Butyl-3-methylimidazole chloride and 3-sulfonate propyl methacrylate potassium salt were mixed in a mass ratio of 1:1, tetramethoxyphenol was added after mixing and dissolved in acetone, and the mixture was stirred, filtered, and concentrated under reduced pressure to obtain BMIM as the main component. + and SPA - of ionic liquid;

[0017] (2) mixing the ionic liquid in step (1) with acrylate in a mass ratio of 1:3, adding 2.5 mol% HDDA and 0.5 mol% TPO, and stirring to obtain an ion gel precursor;

[0018] (3) Spin-coat the photoresist RPN1150 on the thermally oxidized silicon wafer at 4000 rpm, and obtain a square photolithography pattern with a side length of 50*50 μm and a spacing of 5 μm by baking and UV lithography; use RPN1150 photoresist as a mask, under the working pressure of 2 Pa, the ignition pressure of 3 Pa, and the reaction gas of CF 4 and CHF 3 , the flow rates were 10 sccm and 30 sccm, respectively, and the power was 100 W for reactive ion etching. Then, acetone was used to wash away the RPN1150 pattern on the surface, and then the surface was rinsed with deionized water and dried with nitrogen. The silicon wafer was etched with a 25% TMAH solution in a water bath at 80°C using the silicon oxide pattern as a mask. After 4 hours, the pyramid etching was completed to obtain a pyramid silicon template.

[0019] (4) Spin-coat SU-8 2025 with a thickness of 50 μm on the ITO / PET surface at 2000 rpm. After baking, use an MJB4 UV lithography machine at an exposure power of 17 mw / cm 2 Expose for 7 seconds, develop and blow dry to obtain a 1*0.5 cm rectangular patterned half-exposed SU-8 photoresist;

[0020] (5) Add the ion gel precursor prepared in step (2) onto the pyramid silicon template, attach ITO / PET, and place it in a UV light box with an exposure power of 50 mw / cm 2 The semi-cured ion gel and the semi-exposed SU-8 photoresist were laminated and placed in a UV light box under a pressure of 10 KPa at an exposure power of 50 mw / cm 2 The ion gel was exposed to light for 30 min to complete the adhesion between the SU-8 photoresist, and finally a pressure sensor with a stable interface was obtained.

[0021] Furthermore, any one of the preparation methods can produce a low hysteresis capacitive pressure sensor with stable interface adhesion.

[0022] Furthermore, the low hysteresis capacitive pressure sensor with stable interface adhesion is used in flexible electronic devices.

[0023] Compared with the prior art, the advantages of the present invention are as follows:

[0024] 1) The silicon pyramid template prepared by the present invention adopts plasma dry etching SiO 2 The layer causes less damage to the photoresist and the spacing between the pyramids is narrower.

[0025] 2) The present invention can achieve interfacial adhesion of heterogeneous materials by spin coating SU-8 photoresist and controlling the ultraviolet exposure time of ion gel and SU-8 photoresist without the need for additional crosslinking agents or surface treatment, is compatible with micromachining technology, and distinguishes the adhesion area and the sensing area through photolithographic patterning, which is more conducive to device miniaturization and array integration.

[0026] 3) The present invention uses secondary exposure to achieve interface adhesion, so that the change in contact area between the ion gel and the ITO lower electrode during the pressure process is reduced, and the energy dissipation is reduced, resulting in the pressure sensor achieving a low hysteresis pressure-capacitive response. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the structure of the thin film pressure sensor of the present invention.

[0028] Figure 2 This is a physical picture of the pyramid silicon template prepared by the present invention.

[0029] Figure 3 This is the infrared spectrum of SU-8 obtained under different exposure times in the present invention.

[0030] Figure 4 The infrared spectra of the ion gel obtained in the present invention at different UV exposure times are shown.

[0031] Figure 5 This is a physical picture of the SU-8 photoresist photolithography patterning obtained by the present invention after UV exposure for 7 seconds.

[0032] Figure 6 This is a real picture of the semi-cured ion gel obtained by the present invention with an exposure time of 7 minutes.

[0033] Figure 7 The present invention obtains a physical picture of the adhesion pyramid microstructure.

[0034] Figure 8 This is a physical picture of the non-adhesion pyramid microstructure obtained by the present invention.

[0035] Fig. 9 This is a comparison diagram of the interface toughness after adhesion obtained in the present invention.

[0036] Fig.10 This is a comparison diagram of the shear strength after adhesion obtained in the present invention.

[0037] Fig.11 This is a physical picture of the flexible pressure sensor obtained by the present invention.

[0038] Fig.12 This is the pressure-capacitance response diagram of the pressure sensor with a stable interface obtained by the present invention.

[0039] Fig.13This is a response time diagram of the pressure sensor with a stable interface obtained by the present invention.

[0040] Fig.14 This is a graph showing the minimum detection limit of the pressure sensor with a stable interface obtained by the present invention. DETAILED DESCRIPTION

[0041] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0042] Unless otherwise specified, the raw materials or reagents used in the following examples are commercially available products.

[0043] The performance tests of the pressure sensors prepared in the following embodiments are as follows:

[0044] The test method of interface toughness is: 90° peeling test, the PET / ITO / ion gel / SU-8 / ITO / PET structure after secondary exposure, the sample width is 2 cm; one side of the ITO / PET electrode is fixed on the stretching machine, and the other side of the ITO / PET electrode is bent 90° and then pulled vertically upward to obtain the curve of tension and pulling displacement, which is substituted into the formula ,in is the interface toughness, F is the tensile stress, is the peeling angle, and b is the pattern width.

[0045] Shear strength test: After double exposure, the PET / ITO / ion gel / SU-8 / ITO / PET structure was overlapped with 1 cm 2 One side of the ITO / PET electrode is fixed on the stretching machine, and the other side of the ITO / PET electrode is pulled upward in parallel. The curve of tension and pulling displacement is obtained and substituted into the formula , where P is shear strength, F is tensile stress, and S is the bonding area.

[0046] Example 1

[0047] A method for preparing a low hysteresis capacitive pressure sensor with stable interface adhesion, the steps are as follows:

[0048] (1) 1-Butyl-3-methylimidazolium chloride and 3-sulfonic acid propyl methacrylate potassium salt were mixed in a mass ratio of 1:1 to obtain a mixed powder; 20 g of the mixed powder was added with 11.6 mg of tetramethoxyphenol (MEHQ) and dissolved in 50 mL of acetone, stirred at room temperature for 24 h, filtered, and concentrated under reduced pressure to obtain BMIM + and SPA - Ionic liquid as the main component;

[0049] (2) The ionic liquid in step (1) was mixed with methyl acrylate (MA) at a mass ratio of 1:3, 2.5% by mole of 1,6-ethylene glycol diacrylate (HDDA) crosslinker and 0.5% by mole of photoinitiator (TPO) were added, and the mixture was stirred at a speed of 2000 r / min for 24 hours to obtain an ion gel precursor;

[0050] (3) Use acetone, ethanol, and deionized water to clean the 4-inch <100> The 100 nm thermally oxidized silicon wafer was cleaned, and then the photoresist RPN1150 was spin-coated at 4000 rpm, and then baked at 115 °C for 1 min and UV-lithography was performed to obtain a square lithography pattern (square side length 50*50 μm, spacing 5 μm);

[0051] (4) Using RPN1150 photoresist as a mask, reactive ion etching was performed with a working pressure of 2 Pa, a starting pressure of 3 Pa, and a reaction gas of CF 4 and CHF 3 , flow rates were 10 sccm and 30 sccm, respectively, and the power was 100 W; then acetone was used to wash away the RPN1150 pattern on the surface, rinsed with deionized water, dried with nitrogen, and the silicon oxide pattern was used as a mask. In a water bath at 80°C, a 25% TMAH solution was used to etch the silicon wafer. After 4 hours, the pyramid etching was completed to obtain a pyramid silicon template, such as Figure 2 As shown;

[0052] (5) Spin coat SU-8 2025 (50 μm thick) on the ITO / PET surface at 2000 rpm, bake at 95 °C for 2 min, and use an MJB4 UV lithography machine (exposure power 50 mw / cm 2 ) Expose for 7 seconds, develop and blow dry to obtain a patterned half-exposed SU-8 photoresist, the pattern is a rectangle of 1*0.5 cm;

[0053] (6) Add the prepared ion gel precursor onto the silicon template treated with a release agent, attach ITO / PET, and place it in a UV light box (exposure power 50 mw / cm 2 ) for 7 min, peel off the ITO / PET and the semi-cured ion gel with pyramid structure attached thereto; laminate the semi-cured ion gel with the semi-exposed SU-8 photoresist and place it in a UV light box under a pressure of 10 KPa (exposure power 50 mw / cm 2) for 30 min. Due to the insufficient UV exposure dose of the two polymers, ion gel and SU-8, there are uncrosslinked free monomers in each of them. After bonding, the free monomers diffuse with each other at the interface. After secondary exposure, the free monomers cross-link into chains and form a chain entanglement structure in the interface area, thereby achieving an adhesion effect, completing the adhesion of ion gel and SU-8 photoresist, and finally obtaining a pressure sensor with a stable interface, such as Figure 1 shown.

[0054] Example 2

[0055] Only the first UV exposure time of the SU-8 photoresist was changed to 8.5 seconds, and the other schemes were the same as those in Example 1.

[0056] Example 3

[0057] Only the first UV exposure time of the ion gel was changed to 10 min, and the other schemes were the same as Example 1.

[0058] Comparative Example 1

[0059] A simple sandwich structure stacking method is adopted, and after the ion gel is completely cured, it is directly covered on the ITO / PET bottom electrode to obtain a pressure sensor.

[0060] The pressure sensors prepared in Examples 1 to 3 and Comparative Example 1 were subjected to interface performance tests, and their interface toughness and shear strength were tested. The test results are shown in Tables 1 and Fig. 9 , 10 shown.

[0061] Table 1 Performance test results of the pressure sensor prepared by the present invention

[0062]

[0063] As shown in Table 1, there are obvious differences in the performance of the pressure sensors obtained by adjusting the exposure dose between Examples 1 to 3. The highest interface toughness after adhesion obtained in Example 1 is 298.2 Nm. -1 The obtained post-adhesion shear strength reached a maximum of 94.75 kPa.

[0064] From the comparison between the embodiments of the present invention and the comparative examples, it can be seen that the pressure sensor prepared by the present invention is obviously superior to the comparative example in performance, and the present invention can achieve interface adhesion of heterogeneous materials by spin coating SU-8 photoresist and controlling the ultraviolet exposure time of ion gel and SU-8 photoresist without additional cross-linking agent or surface treatment, and does not require additional time for processing and other processes.

[0065] Depend on Figure 3 It can be seen that 915cm -1The characteristic peaks of the nearby epoxy groups become higher as the UV exposure time decreases, indicating an increase in the number of uncross-linked epoxy group monomers.

[0066] Depend on Figure 4 It can be seen that 1636cm -1 Nearby is the characteristic peak of carbon double bond; as the UV exposure decreases, the characteristic peak of carbon double bond becomes higher, indicating an increase in uncross-linked acrylic monomers.

[0067] Depend on Figure 5 It can be seen that the SU-8 photoresist exposed to UV for 7 seconds has a clear and distinct lithographic pattern.

[0068] Depend on Figure 6 It can be seen that the semi-cured ion gel with an exposure time of 7 minutes has an obvious pyramid microstructure.

[0069] Depend on Figure 7 It can be seen that the tip of the ion gel pyramid is pinned to the surface of the SU-8 photoresist.

[0070] Depend on Figure 8 It can be seen that there is a clear boundary between the non-adhesion process gel and the pyramid tip.

[0071] Depend on Fig.11 It can be seen that the obtained flexible pressure sensor does not show interface separation under bending conditions.

[0072] Depend on Fig.12 It can be seen that the sensitivity of the pressure sensor is 0.034 kPa -1 , R 2 =99.92%, hysteresis 4.8%.

[0073] Depend on Fig.13 It can be seen that the pressure sensor has a response time of 16 ms and a recovery time of 15 ms under a 2 kPa pressure shock.

[0074] Depend on Fig.14 It can be seen that the minimum detection limit of the sensor is 0.1Pa.

[0075] The invention laminates a semi-cured ion gel attached to ITO / PET and a semi-exposed SU-8 / ITO / PET and then performs secondary exposure. Due to insufficient ultraviolet exposure doses of the two polymers, the ion gel and SU-8, respectively, there are uncrosslinked free monomers in the two polymers. After laminating, the free monomers diffuse mutually at the interface. After secondary exposure, the free monomers are cross-linked into chains and form a chain entanglement structure in the interface region, thereby achieving an adhesion effect. Since the SU-8 photoresist is subjected to photolithography patterning, the ITO lower electrode is exposed, so that the ion gel and the ITO lower electrode obtain a pressure-capacitance response by changing the contact area during the compression of the prepared capacitive pressure sensor. The sensor is bent, and no interface shedding occurs. Due to interface adhesion, the contact area change amount between the ion gel and the ITO lower electrode during the compression process is reduced, and the adhesion between the gel and ITO is relatively low, resulting in a relatively low hysteresis of the pressure-capacitance response curve.

[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a low hysteresis capacitive pressure sensor with stable interface adhesion, characterized in that: The ionic liquid is mixed with methyl acrylate, and after adding a crosslinker and an ultraviolet photoinitiator and stirring, an ion gel precursor is obtained; the SiO2 layer is dry-etched by plasma to prepare a silicon pyramid template; by spin coating photoresist and controlling the ultraviolet exposure time of the ion gel and photoresist, the interface of heterogeneous materials can be adhered without the need for additional crosslinkers or surface treatment, and finally a pressure sensor with a stable interface is obtained.

2. The method for preparing a low hysteresis capacitive pressure sensor with stable interface adhesion according to claim 1, characterized in that: The main component of the ionic liquid is BMIM + and SPA - The ionic liquid is prepared by mixing 1-butyl-3-methylimidazole chloride and 3-sulfonate propyl methacrylate potassium salt, adding tetramethoxyphenol and dissolving in acetone.

3. The method for preparing a low hysteresis capacitive pressure sensor with stable interface adhesion according to claim 1, characterized in that: The mass ratio of the ionic liquid to methyl acrylate is 1:

3.

4. The method for preparing a low hysteresis capacitive pressure sensor with stable interface adhesion according to claim 1, characterized in that: The crosslinking agent is HDDA, and the ultraviolet light initiator is TPO; the molar ratio of the crosslinking agent is 2.5%; and the molar ratio of the ultraviolet light initiator is 0.5%.

5. The method for preparing a low hysteresis capacitive pressure sensor with stable interface adhesion according to claim 1, characterized in that: The method of preparing a silicon pyramid template by plasma dry etching of SiO2 layer is as follows: using RPN1150 photoresist as a mask, using reactive ion etching, working pressure 2Pa, starting pressure 3Pa, reaction gases CF4 and CHF3, flow rates of 10 sccm and 30 sccm respectively, power 100 W; using silicon oxide pattern as a mask, using a 25% TMAH solution at 80°C in a water bath to etch the silicon wafer to obtain a pyramid silicon template.

6. The method for preparing a low hysteresis capacitive pressure sensor with stable interface adhesion according to claim 1, characterized in that: The photoresist RPN1150 was spin-coated on the thermally oxidized silicon wafer at 4000 rpm; and SU-8 2025 was spin-coated on the ITO / PET surface at 2000 rpm with a thickness of 50 μm.

7. The method for preparing a low hysteresis capacitive pressure sensor with stable interface adhesion according to claim 1, characterized in that: Use MJB4 UV photolithography machine to expose ITO / PET with spin-coated SU-8 2025 for 7 seconds; use UV lamp to expose the ion gel precursor attached to ITO / PET for 7 minutes; then laminate the semi-cured ion gel with the semi-exposed SU-8 photoresist and expose it with UV lamp for 30 minutes under a pressure of 10 Kpa.

8. The method for preparing a low hysteresis capacitive pressure sensor with stable interface adhesion according to claim 1, characterized in that: Here are the steps: (1) 1-Butyl-3-methylimidazole chloride and 3-sulfonate propyl methacrylate potassium salt were mixed in a mass ratio of 1:1, tetramethoxyphenol was added after mixing and dissolved in acetone, and the mixture was stirred, filtered, and concentrated under reduced pressure to obtain BMIM as the main component. + and SPA - of ionic liquid; (2) mixing the ionic liquid in step (1) with acrylate in a mass ratio of 1:3, adding 2.5 mol% HDDA and 0.5 mol% TPO, and stirring to obtain an ion gel precursor; (3) Spin-coat the photoresist RPN1150 on the thermally oxidized silicon wafer at 4000 rpm, and obtain a square photolithography pattern with a side length of 50*50 μm and a spacing of 5 μm by baking and UV lithography; use the RPN1150 photoresist as a mask, and perform reactive ion etching at a working pressure of 2 Pa, a ignition pressure of 3 Pa, and reaction gases of CF4 and CHF3 with flow rates of 10 sccm and 30 sccm, respectively, at a power of 100 W. Then, use acetone to wash off the RPN1150 pattern on the surface, rinse with deionized water, and blow dry with nitrogen. Use the silicon oxide pattern as a mask and etch the silicon wafer with a 25% TMAH solution in a water bath at 80°C. After 4 hours, the pyramid etching is completed to obtain a pyramid silicon template; (4) Spin-coat SU-8 2025 with a thickness of 50 μm on the ITO / PET surface at 2000 rpm. After baking, use an MJB4 UV lithography machine at an exposure power of 17 mw / cm 2 Expose for 7 seconds, develop and blow dry to obtain a 1*0.5 cm rectangular patterned half-exposed SU-8 photoresist; (5) Add the ion gel precursor prepared in step (2) onto the pyramid silicon template, attach ITO / PET, and place it in a UV light box with an exposure power of 50 mw / cm 2 The semi-cured ion gel and the semi-exposed SU-8 photoresist were laminated and placed in a UV light box under a pressure of 10 KPa at an exposure power of 50 mw / cm 2 The ion gel was exposed to light for 30 min to complete the adhesion between the SU-8 photoresist, and finally a pressure sensor with a stable interface was obtained.

9. A capacitive pressure sensor with stable interface adhesion and low hysteresis prepared by the preparation method according to any one of claims 1 to 8.

10. Application of the low hysteresis capacitive pressure sensor with stable interface adhesion according to claim 9 in flexible electronic devices.